Effects of rapid maxillary expansion with six months of retention and no further orthodontic treatment - Micheletti, Kelly Regina [UNESP]; Vessoni Iwaki, Lilian Cristina; Arias Provenzano, Maria Gisette; Cuoghi, Osmar Aparecido [UNESP]; Ramos, Adilson Luiz (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2016)
Previous investigations addressing the long-term effects of rapid or slow expansion on the face and teeth involved the use of a orthodontic fixed appliance following expansion therapy. The present study evaluated changes in dentoskeletal aspects following rapid maxillary expansion (RME) and determine the stability of these changes over three years of follow up. Ten children with bilateral posterior crossbite were evaluated (experimental group). Dental casts and lateral cephalograms were evaluated prior to RME (T0) as well as three months (T1), one year (T2) and three years (T3) after RME. The measures were compared to a control group composed of 21 individuals using ANOVA and the Student's t-test (p > 0.05). Changes on the transverse plane revealed significant expansion of the upper dental arch three months after RME, stable after three years. Expansion at the cusp level was similar to that at the gingival level. No significant changes were found in the angular and linear cephalometric measures among T0, T1, T2 and T3, and in comparison to the control group (p > 0.05). We concluded that early RME produces stable transverse increases in the upper arch after three years without significantly altering sagittal and vertical dentoskeletal relationships, and neither inclined teeth.
Keywords: maxillary expansion; palatal expansion technique; orthodontics interceptive; cephalometrics